RELEVANSI ANTARA MATERI PEMBELAJARAN MENULIS DALAM BUKU PELAJARAN KELAS 5 SEKOLAH DASAR DAN KOMPETENSI DASAR KURIKULUM 2013 - Syamsul Ghufron; Rudi Umar Susanto; Nafiah Nafiah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
The purpose of this study was to describe the relevance of writing learning materials in the grade 5 textbooks of elementary schools and the basic competencies of the 2013 Curriculum. This research is library research (library research), which is research based on searching the literature related to the issues to be discussed. The approach used in this study is a qualitative approach. The results of the data analysis show that between the writing learning material in the 5th grade textbooks of elementary schools and the basic competencies of the 2013 Curriculum, there is a very significant relevance. This conclusion is based on the results of data analysis on two research problems which show the following results: (1) There is a very significant relevance between writing learning materials in grade 5 textbooks of elementary schools and basic competencies of knowledge in the 2013 curriculum; (2) There is a very significant relevance between writing learning materials in grade 5 textbooks of elementary schools and basic competency skills in the 2013 curriculum.